Growing and Archiving Youth Aspirations: Efforts of C20 Community in Preserving Surabaya Heritage - Rahmad Hidayat (MOZAIK HUMANIORA, 2016)
The paper attempts to highlight the efforts of C20 community in Surabaya to actively ‘remind’ Surabaya youngsters especially to their own identity as the heirs of Surabaya, which is rich in its coastal urban traditions such as culinaries, buildings, and the plurality of the people. Its base camp, located on Cipto street number 20 (which explains how it gets its name from), is a place to record and publish through activities in public spaces, such as Ayorek.org, a site to gather any facts and values about Surabaya which seem to be forgotten by Surabaya young people. The paper specifically focuses on the way youngsters involved in the community are aspired to (re)capture their identities and find their place in this global world. By doing qualitative research, I interviewed the members of community and was also involved in their activities in Surabaya. It is argued that the community of C20 in Surabaya is filling the empty space left by the Surabaya government in empowering the youth to preserve their own city. C20 is also successful in creating a place for youth aspirations not only to “memorize” Surabaya but also to make Surabaya a better place to live and to be creative.